Free convective heat transfer in Jeffrey fluid with suspended nanoparticles and Cattaneo–Christov heat flux. Issue 3 (July 2020) - Vasu, B; Ray, Atul Kumar; Gorla, Rama SR
Free convection flow of Jeffrey nanofluid past a vertical plate with sinusoidal variations of surface temperature and species concentration is presented. The study of heat transfer and nanofluid transport has been done by employing Cattaneo–Christov heat flux model and Buongiorno model, respectively. Equations governing the flow are non-dimensionalized using appropriate transformations. Furthermore, the method of local similarity and local non-similarity is used to reduce the equations into non-linear coupled system of equations which are then solved by homotopy analysis method. The obtained results are validated by comparing with the existing results available in the literature. The numerical results are found to be in good agreement. The effects of varying the physical parameters such as Deborah Number, Prandtl number, Schmidt number, thermophoresis parameter, Brownian motion parameter and buoyancy ratio parameter are obtained and presented graphically. The effect of sinusoidal variation of surface temperature and species concentration on the skin friction coefficient, Nusselt number and Sherwood number is also shown. Velocity for Jeffrey nanofluid is more than the Newtonian nanofluid while temperature and nanoparticle concentration for Jeffrey nanofluid is less than the Newtonian nanofluid. Raising value of thermal relaxation times leads to an increase in the heat transfer coefficient. It is observed that temperature of Cattaneo–Christov heat flux model is less than that in classical Fourier's model away from the vertical wall. These types of boundary layer flow problems are found in vertical film solar energy collector, grain storage, transportation and power generation, thermal insulation, gas production, petroleum resources, geothermal reservoirs.